(untitled) (Zaporizhzhia Historical Review, 2021)
The giver research aims to revel the problem, to analyze the system of archetypes directed to forming necessary personality features of the warrior and his military preparation in national image-creating and monumental folk art. The research encompasses definite time spans, which gives a possibility to see the stated archetypes not as sudden temporal phenomena but as an ancient succession system. A wide spreading of the given archetypes among our people shows that they are demanded and significant. That’s why to consider this question is an important part in the process of widening knowledge concerning a historic image of the national warrior.